Vertisoles hidromórficos de la planicie costera del río de la Plata, Argentina - Imbellone, Perla Amanda (2011)
Hydromorphic Vertisols are the dominant soils in the coastal plain of the la Plata river, Buenos Aires province, Argentina. Four representative soils in the districts of La Plata, Ensenada and Berazategui were studied. Pedological and sedimentological properties are described and analyzed. The purpose of this contribution is to discuss: a) the grain size distribution and mineralogy of hydromorphic Vertisols in the rio de la Plata «mudflat»; b) the influence of these properties on the generation of morphological features and c) the associated pedogenic processes that take place. The morphology of the soil is related to vertic and hydromorphic features in the upper and middle horizons of the soil. Moderate and strong wedge-shaped and angular aggregates are abundant in the solum, with interpedal slickensides, sometimes striated, visible at various levels of observation. The matrix can be moderately or dominantly anisotropic and shows zones of optical anisotropism that run through the fine material with variegated patterns or anisotropic aureoles surrounding the pores. Hydromorphism is favoured by frequent pluvial flooding, the level landscape and the high water table, which is generally between 0.80 and 1.20 m deep. Therefore, endosa-turation or episaturation can occur at different times of the year. Soils have a variety of redoximorphic features, mainly reduced matrices (2.5Y, 5Y hues; chromas of 2 or less), redox concentrations of manganese and iron as nodules and concretions, surface impregnations of sesquioxides on the peds and some dark subsurface accumulations and ramifications through the matrix; there are also some depleted zones in the matrix. Concretions are hard in hand specimens and occur within the matrix; segregations are soft in hand specimens and they appear in thin sections as impregnations of the matrix with diffuse boundaries. They appear as mottles in the field. Soil textural class is clay. Fine clay markedly predominates over coarse clay. Soils are illitic Vertisols with a very high total clay content which have generated vertic features. The hydromorphic influence is manifested by the type and abundance of redoximorphic features, which are related to the degree of hydromorphism within each profile and the associated properties.